Hifened Analytical Techniques in the Identification of Chemical Markers and Adulterations in Natural Products - Storion, Ana Carolina; Goncalves, Carolina Passarelli; Marcucci, Maria Cristina [UNESP] (Brazilian Chemical Soc, 2020)
The use of phytotherapic and herbal medicines has increased in recent years. Because of the growing demand, quality control for these drugs becomes increasingly necessary. The most widely practice used nowadays for standardization of products of plant origin is the identification of the phytochemical markers that, are characteristic for each species. However, such methodology can be inefficient, as many markers have no relationship with the biological activity of each plant. The simultaneous use of some already known analytical techniques not only can be an alternative to the quality control of these phytopharmaceuticals but also results in evaluation of these chemical compounds in its entirety. This work is a literature review, which evaluated different coupled analytical methods - which, reported better sensitivity, ease and accuracy in analysis - to highlight the most appropriate methodology to identify possible adulterations in herbal drugs and phytotherapics to ensure its efficacy, safety and quality to consumers. The data generated from these hyphenated analytical techniques and, the use of chemometrics, result in more valuable information regarding the authenticity of the plants used in the fabrication of herbal medicinal products. Modern analytical methods such as HPLC and UHPLC when used simultaneously with MS, RMN and chemometrics generate more precise and faithful results in the referred analysis and are useful tools in the identification of adulteration in herbal drugs and phytotherapics.
Keywords: Medicines; hyphenated analytical methods; chemometrics; quality control